some noun paradigms - Dagny Hildegard Skaile; Joshua Karl Wilbur (Joshua Wilbur, 2011)
Linguistic documentation of the Pite Saami language (ISO693-3: sje) noun paradigms for guolle (fish), guolátj (fish-DIM), guolla (testicle), guolatj (testicle-DIM), vájbmo (heart), sallte (salt)